Drafting contracts : how and why lawyers do what they do - Stark, Tina L., 1953- (New York : Wolters Kluwer Law & Business, 2014)
"Reflecting real-world transactional practice, Tina L. Stark emphasizes the importance of drafting a contract that accurately memorializes the business deal while advancing a client's interests. This timely second edition of Drafting Contracts : How and Why Lawyers Do What They Do, features many new and updated exercises, examples, and precedents"--Unedited summary from book cover.
Drafting clearly and unambiguously: Legalese -- Clarity through format -- Clarity through sentence structure -- Ambiguity -- Numbers and financial provisions -- A potpourri of other drafting considerations -- Deconstructing complex provisions -- Drafting from the client's perspective. Adding value to the deal -- Putting a contract together. Organizing a contract and its provisions -- The drafting process -- How to review and comment on a contract -- Amendments, consents, and waivers -- Drafting ethically. Ethical issues in drafting -- Additional exercises. Additional exercises -- Exemplars and guided reading exercises. Exemplars and guided reading exercises -- Exhibit : Escrow agreements.
Includes bibliographical references and index.
Keywords: Contracts -- United States; Contracts -- United States -- Language; Legal composition; Contrats -- Etats-Unis.; Redaction juridique; Contracts; Contracts -- Language; Legal composition; United States